Internet of things survey on crop field smart irrigation automation using IOT - Pavan Kumar, T; Kumar Lala, Satyam; Sravani, Boppana; Sandeep, Andru (International Journal of Engineering and Technology, 2018)
This paper gives a general survey on Crop Field Smart Irrigation Mechanization utilizing web from claiming things. The paper covers details regarding the basics of Internet of Things and also the importance of Agriculture in a country like India. Internet of Things is fundamentally those intercontinental for everyone electronic units through Internet. By this interconnection the devices work in a synchronous way to achieve common goals. It is an evolving technology in the areas of trade, industry, medical and many applications. Many applications of IoT make use of sensors for detecting and activating gadgets helping in sharing of data. Agriculture is one such trade on which the entire nation is dependent. We in brief review the various techniques which will allow the farmers to grow more of their crops and reduce wastage of water by using sensors and automation of the irrigation system. The irrigation of crop fields depends on the data collected by the soil moisture sensors. The review can also be extended by understanding the way light intensity is controlled in greenhouses and also that the farmers can be able to monitor the field conditions from anywhere. This system is very useful in areas with scarcity of water. This sys is 92% more efficient than the conventional approach.